2018
DOI: 10.1016/j.snb.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Pd-assisted H2 detection of ZnO nanorod gas sensor with enhanced sensitivity and stability

Abstract: J, et al. (2018) Amorphous Pdassisted H 2 detection of ZnO nanorod gas sensor with enhanced sensitivity and stability. Sensors and Actuators B: Chemical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…These SMON sensing materials mainly include ZnO, 31,32 CuO, [33][34][35][36] SnO 2 , 37-39 TiO 2 , 40,41 Fe 2 O 3 , 42,43 In 2 O 3 , 44-47 Co 3 O 4 48-50 and WO 3 . 18,51 For further improvement of sensing performance, they have been modified using noble metals, [52][53][54][55] metal ions, [56][57][58][59][60] and carbon materials. [61][62][63][64] Composites of multi-phase SMONs [65][66][67] have also been frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…These SMON sensing materials mainly include ZnO, 31,32 CuO, [33][34][35][36] SnO 2 , 37-39 TiO 2 , 40,41 Fe 2 O 3 , 42,43 In 2 O 3 , 44-47 Co 3 O 4 48-50 and WO 3 . 18,51 For further improvement of sensing performance, they have been modified using noble metals, [52][53][54][55] metal ions, [56][57][58][59][60] and carbon materials. [61][62][63][64] Composites of multi-phase SMONs [65][66][67] have also been frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 Various methods and technologies have been applied to synthesize ZnO nanorods, such as thermal evaporation, 2 laser ablation, 3 chemical vapor deposition, 4 arc plasma reaction, 5 and solution methods. 6 Moreover, to achieve an enhanced sensing performance of ZnO nanorods, numerous materials have been applied as coatings on the surface of ZnO nanorod gas sensors, like Pd, 7 InSb, 8 Ni, 9 etc.…”
mentioning
confidence: 99%
“…However, room temperature‐operated H 2 gas sensors were demonstrated with a high selectivity toward H 2 gas by using a thin Pd catalytic layer on top of zinc oxide nanowires surface . In our previous work, we found that a 1 nm thick Pd layer was composed of many tiny Pd islands on an IGZO surface and dramatically enhanced H 2 gas detection at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…[51] In our previous work, we found that a 1 nm thick Pd layer was composed of many tiny Pd islands on an IGZO surface and dramatically enhanced H 2 gas detection at room temperature. [51] In our previous work, we found that a 1 nm thick Pd layer was composed of many tiny Pd islands on an IGZO surface and dramatically enhanced H 2 gas detection at room temperature.…”
Section: Igzo-based H 2 Sensors On the Pmma Substrate And Their Bendimentioning
confidence: 93%